2022
DOI: 10.1187/cbe.21-05-0136
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Retention of Transgender and Gender Nonconforming Students in Undergraduate STEM Majors

Abstract: Science, technology, engineering, and mathematics (STEM)majors do not retain transgender and gender nonconforming (TGNC) students and cisgender students at similar rates. This article explores TGNC retention in STEM majors and describes factors that contribute to differential retention of cisgender and TGNC students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…Existing research is mixed on how well the gender parity for men and women in a STEM field predicts the presence of queer-spectrum individuals, and thus the patterns of under-representation in our data may be a systemic STEM-wide problem and may follow different patterns than the patterns of under-representation of women [ 1 , 5 , 20 ]. Yoder and Mathesis [ 26 ] found that the percentage of women in a field was correlated with the likelihood that lesbian, gay, or bisexual individuals disclosed their queer identity to colleagues, which is different from predicting overall numbers of LGB individuals, but does provide some information about climate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Existing research is mixed on how well the gender parity for men and women in a STEM field predicts the presence of queer-spectrum individuals, and thus the patterns of under-representation in our data may be a systemic STEM-wide problem and may follow different patterns than the patterns of under-representation of women [ 1 , 5 , 20 ]. Yoder and Mathesis [ 26 ] found that the percentage of women in a field was correlated with the likelihood that lesbian, gay, or bisexual individuals disclosed their queer identity to colleagues, which is different from predicting overall numbers of LGB individuals, but does provide some information about climate.…”
Section: Discussionmentioning
confidence: 99%
“…Sansone and Carpenter [ 32 ] found a higher number of men in same-sex couples in STEM fields that have higher proportions of women. But, conversely, Malory and Hughes [ 5 ] found the lowest representation of trans and non-binary students in biology classes, and Cech And Waidzunas (2021) found no relationship between representation of queer-spectrum individuals and STEM field. Therefore, it would be erroneous to assume that underrepresentation is a problem limited to engineering and computer science or that the under-representation of queer-spectrum individuals inherently parallels the underrepresentation of women in STEM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations